Towards providing middleware-level proactive resource reorganisation for elastic HPC applications in the cloud. (2019) - Da Rosa Righi, Rodrigo; Rodrigues, Vinicius Facco; De Nardin, Igor Fontana; Da Costa, Cristiano André; Alves, Marco Antonio Zanata; Pillon, Maurício Aronne
Elasticity is one of the most important features of cloud computing, referring to the ability to add or remove resources according to the needs of the application or service. Particularly for High Performance Computing (HPC), elasticity can provide a better use of resources and also a reduction in the execution time of applications. Today, we observe the emergence of proactive initiatives to handle the elasticity and HPC duet, but they present at least one problem related to the need of a previous user experience, large processing time or completion of parameters. Concerning the aforesaid context, this paper presents ProElastic - a lightweight model that uses proactive elasticity to drive resource reorganisation decisions for HPC applications. Our idea is to explore both performance and adaptivity at middleware level in an effortless way at user perspective. The results showed performance gains and a competitive cost (application time consumed resources).